Cohort profile: the Right to Care Clinical HIV Cohort, South Africa. Issue 6 (10th June 2017) - Fox, Matthew P; Maskew, Mhairi; Brennan, Alana T; Evans, Denise; Onoya, Dorina; Malete, Given; MacPhail, Patrick; Bassett, Jean; Ebrahim, Osman; Mabotja, Dikeledi; Mashamaite, Sello; Long, Lawrence; et al.
Abstract : Purpose: The research objectives of the Right to Care Clinical HIV Cohort analyses are to: (1) monitor treatment outcomes (including death, loss to follow-up, viral suppression and CD4 count gain among others) for patients on antiretroviral therapy (ART); (2) evaluate the impact of changes in the national treatment guidelines around when to initiate ART on HIV treatment outcomes; (3) evaluate the impact of changes in the national treatment guidelines around what ART regimens to initiate on drug switches; (4) evaluate the cost and cost-effectiveness of HIV treatment delivery models; (5) evaluate the need for and outcomes on second-line and third-line ART; (6) evaluate the impact of comorbidity with non-communicable diseases on HIV treatment outcomes and (7) evaluate the impact of the switch to initiating all patients onto ART regardless of CD4 count. Participants: The Right to Care Clinical HIV Cohort is an open cohort of data from 10 clinics in two provinces within South Africa. All clinics include data from 2004 onwards. The cohort currently has data on over 115 000 patients initiated on HIV treatment and patients are followed up every 3–6 months for clinical and laboratory monitoring. Findings to date: Cohort data includes information on demographics, clinical visit, laboratory data, medication history and clinical diagnoses. The data have been used to identify rates and predictors of first-line failure, to identify predictors of mortality for patients on second-line (eg, low CD4 counts) and to show that adolescents and young adults are at increased risk of unsuppressed viral loads compared with adults. Future plans: Future analyses will inform national models of HIV care and treatment to improve HIV care policy in South Africa.